Flash boys a Wall Street revolt - Lewis, Michael frey50 (New York W.W. Norton & Company, 2014)
A small group of Wall Street guys who figure out that the U.S. stock market has been rigged for the benefit of insiders the big Wall Street banks expose this institutionalized injustice and go to war to fix it.
Introduction: windows on the world -- Hidden in plain sight -- Brad's problem -- Ronan's problem -- Tracking the predator -- Putting a face on HFT -- How to take billions from Wall Street -- An army of one -- The spider and the fly -- Epilogue: riding the Wall Street trail.
Keywords: Stockbrokers -- United States; Finance -- United States -- History -- 21st century; Wall Street (New York, N.Y.)